The use of muscle near-infrared spectroscopy in sport, health and medical sciences: recent developments - Hamaoka,T.; McCully, K. K.; Niwayama, M.; Chance, B. (Philosophical Transactions A, 2011)
Near-infrared spectroscopy (NIRS) has been shown to be one of the tools that can measure oxygenation in muscle and other tissues in vivo. This review paper highlights the progress, specifically in this decade, that has been made for evaluating skeletal muscle oxygenation and oxidative energy metabolism in sport, health and clinical sciences. Development of NIRS technologies has focused on improving quantification of the signal using multiple wavelengths to solve for absorption and scattering coefficients, multiple pathlengths to correct for the influence of superficial skin and fat, and time-resolved and phase-modulated light sources to determine optical pathlengths. In addition, advances in optical imaging with multiple source and detector pairs as well as portability using small wireless detectors have expanded the usefulness of the devices. NIRS measurements have provided information on oxidative metabolism in various athletes during localized exercise and whole-body exercise, as well as training-induced adaptations. Furthermore, NIRS technology has been used in the study of a number of chronic health conditions. Future developments of NIRS technology will include enhancing signal quantification. In addition, advances in NIRS imaging and portability promise to transform how measurements of oxygen utilization are obtained in the future.